Hearing enslaved voices
1 online resource (viii, 256 pages)
Keywords: "This book focuses on alternative types of slave narratives, especially courtroom testimony, and interrogates how such narratives were produced, the societies (both those that were majority slave societies and those in which slaves were a distinct minority of the population) in which testimony was permitted, and the meanings that can be attached to such narratives. The chapters in this book provide valuable information about the everyday lives-including the inner and spiritual lives-of enslaved African American and Native American individuals in the British and French Atlantic World, from Canada to the Caribbean. It explores slave testimony as a form of autobiographical narrative, and in ways that allow us to foreground enslaved persons' lived experience as expressed in their own words"--